Pengaruh Kualitas Sumber Daya Manusia Dan Pengalaman Kerja Terhadap Etos Kerja Pada Surabaya Grammar School - Andreansah Andreansah; Achmad Daengs GS; Sugiharto Sugiharto; Rina Dewi (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
Quality human resources and work experience relevant to the workload have a positive impact on accelerating the company's goals. Human resources act as assets that have the ability of reason, knowledge, and motivation that must be supervised by management so that their work ethic can contribute to the achievement of company goals. On the other hand, an employee's work experience is also an indicator that can be put forward to achieve company goals. Employees with high work experience are expected to help the company to educate other employees on how to understand and complete work in a structured manner and produce output as expected. Referring to these descriptions, the study aims to examine the impact of work experience and HR quality on the work ethic of Surabaya Grammar School employees. The results of the study using a sample of 100 employees and analyzed using multiple linear regression with t-test and f-test concluded that work experience and HR quality have a significant positive impact on the work ethic of Surabaya Grammar School employees partially and simultaneously